English learning motivating and demotivating factors among post-socialist Mongolia's future English teachers - Shagdarsuren, Solongo (Englisia Journal, 2020)
A declining number of credit hours of English courses for English-majoring students at the National University of Mongolia lead teachers and students to focus on effective English education and what factors would affect it within credit hours allowed at the university. Meanwhile, English teaching class hours in Mongolian secondary schools have been increasing for the last few years, due to the national interest in learning English, resulting in a greater demand for English teachers. This study investigated the motivation of Mongolian English-majoring students towards learning English and the factors affecting them to be demotivated. A total of 20 students majoring in English teaching at the National University of Mongolia, Erdenet School of the 2019/2020 academic year completed the questionnaire on English learning motivation and attended focus group interviews. The findings showed that the students had instrumental orientation and demonstrated a strong desire to learn English. However, they felt demotivated by their teachers’ and classmates’ attitudes and living situations. The researcher recommends that the students and the teachers create a conducive environment in the classroom, where the students can feel comfortable despite making mistakes, and also suggests other practical takeaways given this post-socialist English learning environment.